Starch/ethylene-co-vinyl alcohol fiber mesh scaffolds: Production, characterization and surface modification - Pashkuleva, I. (2008)
[Excerpt] Tissue engineering scaffolds must provide cell anchorage sites, mechanical stability and structural guidance. Fiber mesh structures have been considered as adequate scaffolds for tissue engineering due their high surface area available for the adhesion and proliferation of different cell types. In addition, they present a good degree of interconnectivity between pores, which is essential for the migration of cells and diffusion of nutrients. Herein, we propose a new route to produce fiber mesh scaffolds from a starch/poly(ethylene-co-vinyl alcohol) (50/50-%wt) blend. Scaffolds with porosity up to 80% were obtained by a simple wet spinning technique based on solution/precipitation of a polymeric blend and subsequent fiber sintering to stabilize the produced 3D structures. The proposed wet spinning procedure avoids thermal degradation, typical for the conventional melt spinning techniques, as shown by thermal gravimetric analysis. [...]